Investigating Perceptions of Pre-Service Teachers and Instructors About TPACK Capabilities of Pre-Service Teachers: An Explanatory Study Among Selected UAE Universities - MOHEBI, LAILA MURTADHA BAQER (2018)
This explanatory mixed-method study aimed at understanding UAE pre-service teachers’ perspectives on their preparedness to use technology for future classroom practices, as well as their instructors’ perspectives on pre-service teachers’ preparedness to use technology for future classroom practices. This study also looks into the pre-service teachers and instructors’ suggestions for future action plan to maximize the preparedness and the factors that they believed influenced the acquisition of knowledge and skills regarding technology integration in the classroom. In addition, the study explores research questions that will both address technology readiness and its affecting factors, for which the Technological Pedagogical and Content Knowledge (TPACK) model was used as a framework to reflect on the technology integration skills of pre-service teacher. The study was conducted in three selective universities in the UAE, where the quantitative data was obtained from a modified survey that was based on Schmidt et al.’s (2009) TPACK survey. A total of 500 surveys were distributed in the three participating universities. Out of these, 359 surveys returned which results in a response rate of 72%. The qualitative data was obtained from interviews with 12 pre-service teachers and 6 instructors. This study used descriptive analysis for the survey and thematic analysis for the interviews to understand the pre-service teachers' and their instructors' perspectives of TPACK. In addition, thematic analysis was used for suggestions and recommendations. Furthermore, to know the factors that influenced the acquisition of knowledge and skills regarding ICT integration in the classroom, independent samples t-test and One-way between groups ANOVA analysis were conducted. The analysis showed that in general, pre-service teachers are confident when it comes to their TPACK capabilities. With the highest mean score of M = 4.12 for Content Knowledge and the lowest mean score of M = 3.68 for Models of TPACK. Moreover, results indicated that the most significant factor that influenced the acquisition of knowledge and skills regarding ICT integration in the classroom was practical experiences in schools. However, the analyses of the interviews of both pre-service teachers and instructors showed that there were some challenges and points for improvement to be considered.